Impact of the COVID-19 pandemic and its related psychological effect on orthopedic surgeries conducted in different types of hospitals in Taiwan. (28th February 2021) - Shih, Chia-Lung; Huang, Peng-Ju; Huang, Hsuan-Ti; Chen, Chung-Hwan; Lee, Tien-Ching; Hsu, Chia-Hao
Aim: Taiwan's response to the coronavirus disease 2019 (COVID-19) differed in that it successfully prevented the spread without having to shutdown or overburden medical services. Patients' fear regarding the pandemic would be the only reason to reduce surgeries, so Taiwan could be the most suitable place for research on the influence of psychological factors. This study aimed to assess the impact of patients' fear on orthopedic surgeries in Taiwan amid the peak period of the COVID-19 pandemic. Patients and Methods: The investigation period included the COVID-19 pandemic (March 2020 to April 2020) and the corresponding period in the previous year. The following data on patients with orthopedic diseases were collected: outpatient visits, hospital admission, and surgical modalities. Results: The COVID-19 pandemic led to a 22%–29% and 20%–26% reduction in outpatients, 22%–27% and 25%–37% reduction in admissions, and 26%–35% and 18%–34% reduction in surgeries, respectively, at both hospitals. The weekly mean number of patients was significantly smaller during the COVID-19 pandemic for all types of surgery and elective surgeries at the university hospital, and for all types of surgery, elective surgeries, and total knee arthroplasties at the community hospital. Further, patients visiting the community hospital during the pandemic were significantly younger, for all types of surgery, elective surgeries, and total knee arthroplasties. Conclusions: The reduction in orthopedic surgeries in Taiwan's hospitals during COVID-19 could be attributed to patients' fear. Even without restriction, the pandemic inevitably led to a reduction of about 20%–30% of the operation volume.